Rice Bran Substitution and Moringa Leaf Powder Addition on Sensory Acceptance Soft Cookies - Mohammad Fatkhurrozi; Raida Amelia Ifadah; Andika Kuncoro Widagdo; Lucia Tri Pangesthi (Universitas Negeri Padang, 2026)
The substitution of rice bran flour and the incorporation of moringa leaf powder were examined in relation to their effects on the sensory acceptability of soft cookies, evaluated across the parameters of color, aroma, taste, and texture. A quantitative experimental design was employed, comprising six treatment combinations: B1K1 (10% rice bran flour and 5% moringa leaf powder), B2K1 (20% rice bran flour and 5% moringa leaf powder), B3K1 (30% rice bran flour and 5% moringa leaf powder), B1K2 (10% rice bran flour and 10% moringa leaf powder), B2K2 (20% rice bran flour and 10% moringa leaf powder), and B3K2 (30% rice bran flour and 10% moringa leaf powder). Preference levels were evaluated by 30 semi-trained panelists through a five-point hedonic test, and all collected data were subsequently analyzed using Two-Way ANOVA. The results indicated that the substitution of rice bran flour did not exert any significant effect on the product's color, aroma, taste, or texture. The addition of moringa leaf powder at a concentration of 10% influenced aroma, taste, and texture as the primary sensory attributes, whereas the addition at 5% produced a significant effect only on aroma, with no notable impact on color, taste, or texture. Moreover, the analytical findings confirmed that no interaction effect existed between the two treatment factors across any of the sensory attributes assessed.